Empowerment of tribal communities through sericulture programmes in Jharkhand State - Setty, H. H. Ninga; Gopal, Dr. Lasya; Chinnaswamy, Prof. K P (IJRDO - Journal of Social Science and Humanities Research, 2019)
Tasar culture is a forest-based tribal oriented industry. It provides income and employment to the rural poor and tribals in Jharkhand and adjoining states in India. The government of Jharkhand has initiated various sericulture development schemes with the support of the Central Silk Board to improve the socio-economic conditions of the people in general and empowerment of tribals in particular. 17 schemes were implemented during the 11th and 12th Five year plan in Jharkhand State by the government. More than 85 per cent of the Tasar rearers belong to tribal community in the pre-cocoon segment. TERI carried out an impact assessment of these programmes including both pre-cocoon and post cocoon segments. This paper discusses the empowerment of tribal people through tasar culture activities especially in the pre-cocoon sectors. The study covered 386 beneficiaries and stakeholders from eight districts by using appropriate tools. The results showed a positive trend with a rapid sericulture growth and involvement of people in this sector. The number of families adopting tasar rearing increased by 15 times, cocoon production by 12 times and silk production by 12 times. Most of the tasar farmers brushed about 200 DFLs per crop. The average income obtained ranged from Rs. 40,000 to 60,000 per annum by Reshamdoot, Rs. 25,000 to 35,000 per annum by seed farmers from two crops and Rs. 10,000 to Rs. 20,000 per annum by commercial and nucleus farmers from one crop. Implementation of theprogrammes has brought positive changes to the socioeconomic condition of the tribal community to a reasonable extent and their empowerment by skilling and knowledge of the sector.